Iron supply for erythropoiesis in the rabbit. - Celada, A (1984)
Marrow radioiron uptake and marrow blood flow were measured in order to evaluate iron supply for erythropoiesis. Normal, phenylhydrazine-treated and bled animals were studied. The plasma iron turnover of seven normal rabbits was 1.49 +/- 0.22 mg/dl whole blood per d, of 11 rabbits treated 4 d before with phenylhydrazine was 5.16 +/- 1.81, and of four bled animals the plasma iron turnover was 3.75 +/- 1.61. The cardiac output and the percentage of blood flow to the marrow was increased in phenylhydrazine-treated and bled animals. Marrow iron flow in phenylhydrazine-treated animals was 38.3 +/- 32.6 micrograms/min per kg as compared with control values of 7.0 +/- 1.3 (P less than 0.01). This was due to an increase in marrow flow, an increase in plasma iron, and an increase in plasmatocrit. In bled animals, in spite of an increased marrow blood flow, marrow iron flow of 7.3 +/- 2.2 was similar to that of control animals due to a lower plasma iron concentration. The calculated marrow iron extraction of 3.7 +/- 2.4% in phenylhydrazine-treated animals was not different from that of control animals of 4.3 +/- 1.1, whereas extraction was increased in bled animals to 7.9 +/- 1.3 (P less than 0.01). In additional studies of transfused animals, acutely induced anemia was associated with an increased cardiac output, but also with a relative decrease in marrow flow, which left marrow iron supply unaffected. It would appear from these studies that an important mechanism for meeting the increased iron requirement of the hyperplastic erythroid marrow is an increase in marrow blood flow.